Platelet-rich plasma in the management of trigger finger: A case report - Medina-Porqueres, Iván; Martin-Garcia, Pablo; Sanz-De-Diego, Sofia; Reyes-Eldblom, Marcelo (Kare Publishing, 2022)
Platelet-rich plasma (PRP) has emerged as a viable therapeutic alternative for a number of clinical applications and has potential benefit for use in trigger finger. However, PRP use has not been previously reported for this condition. We report a 63-year-old woman sustaining a refractory trigger finger after a series of three PRP injections over a 2-week period. There was resolution of triggering, with no symptom recurrence at 3-month follow-up. On the basis of this report, we can assume that the treatment of trigger finger with PRP is a promising therapeutic option to be further explored with larger samples and high-quality studies.
Keywords: Plasma; Dedos - Lesiones y heridas; platelet-rich plasma; trigger finger; Case study; Growth factors